Investigating experiences of transition from a teacher to the head of department - Ogina, Teresa Auma (University of Pretoria, 2018)
The changes in education experienced by Heads of Departments (HoDs) over the past decade remain unprecedented. The available literature suggests that many teachers are promoted to the position of HoD without the relevant training for their new role and yet novice HoDs are expected to make a successful transition to their new position. The literature focuses on the role of HoDs and the challenges they face, in general. However, there seems to be a gap concerning how HoDs experience the transition process from their previous role as teacher to that of HoD. This study sought to investigate the experiences of transition from teacher to Head of Department (HoD) in terms of the perspectives of selected HoDs at public primary schools in the Tshwane South District in Gauteng Province, South Africa. A qualitative case study within a constructivist/interpretivist paradigm was adopted and Bridges’ (1991) theory of transition underpinned this study. Fifteen individual semi-structured interviews were conducted with Foundation and Intermediate Senior Phase (INTERSEN) HoDs from seven public primary schools to generate data to answer the research questions. The findings of this study indicate that during the transition period HoDs experience changes that are both personal, such as financial benefits and status, and work-related which involve changes in their responsibilities and their relationships with former peers. HoDs react differently to these changes. The challenges experienced during transition include the lack of role clarity; a lack of subject knowledge and management and leadership skills; heavy workloads and time constraints; tension between management and leadership and teaching responsibilities; a resistance from teachers; and inadequate support. In order to cope with challenges experienced during the transition process, this study suggests that although HoDs prefer to give little verbal expression to their frustrations, they are committed to work and to self-empowerment; they seek support from school management and family as well as external support from teacher unions; they delegate tasks; and they participate in teamwork. The implications from this study are that HoDs need school-based support from the Department of Basic Education (DBE) as well as emotional support.